Estrategias didácticas de las prácticas de laboratorio y su aporte en las competencias técnicas en instalaciones automatizadas de los estudiantes de electricidad del Colegio de Bachillerato Simón Bolívar de la ciudad de Guayaquil - Jaime Acuria, Ricardo Arnulfo (2019)
The main argument used for the development of this didactic project is to incorporate new components and didactic instruments in the teaching of Automated Installations from the diagnosis collected and to contribute to improving the educational activity to use scientific methods, technological equipment, didactic strategies for the development of activities in the laboratory. This project wants to contribute with a didactic module to improve the learning and academic performance of the students, in this way it constitutes a valid tool to create new laboratory activities that allow to increase their knowledge and technical training. Projects of this type must have the necessary specialized assistance in the academic and pedagogical sector in order to improve the quality of education. The implementation of this didactic guide has great advantages since it offers us basic didactic content for better learning in the specialty and basically in Automated Installations, it is intended to correctly guide students by delivering didactic and methodological strategies that make possible the use of a basic facilities module. It is important to indicate that basic information and reference of the specialty was collected. The constant process in the educational and technological field, currently forces the educational institutions to promote the academic improvement of the students and also of the teachers and constantly update the basic knowledge of didactics, pedagogy, methodologies, considering the role that should be comply.